STRUKTUR PENYAJIAN TARI ZAPIN ARAB (GRUP AL-BADAR) DI PONTIANAK TIMUR KALIMANTAN BARAT - Syarifah Sri Rizki Khairunnisha; Imma Fretisari; Asfar Munir (Universitas Tanjungpura, 2020)
AbstractThe background of this research was to find out the basic and supporting elements found in the Arabic Zapin Dance. The researcher hopes that this research can become a corpus of data documenting the Zapin Arabic Dance so that it can be used as reference by further researchers and readers.The research method used was descriptive method of analysis with the form of qualitative research and choreographic approach. The data of this research was to describe the structure of the Arab Zapin dance. Sources of data include, Syarif Usman, Syarif Mansyur, Sy Ghozali Zein as an artist who knows the structure of the Apara Arab Zainian dance. The data collection techniques were observation, interview, and documentation with researcher as the main instrument. The persistence and triangulation of sources were used to check the validity of data. The data analysis techniques of this research were analysis during the field, data reduction, data presentation, conclusion and classification.The results of this study described the presentation structure of the Arabic Zapin Dance. There are 3 types of motion, divided into initial motion, middle motion (contents) and closing motion. The floor design used is in the form of vertical, horizontal lines. Low design, pure design, angular design, flat design, high design are the top designs used.Keywords: Presentation Structure, traditional zapin Arabic dance.